(untitled) (Journal of Nuclear Technology in Applied Science, 2021)
Ionizing radiations resulting from radioactive materials have widely uses in many applications in variousfields. The industrial applications are as consumer products, industrial radiography using γ-radiographycameras and radiography X-ray and nuclear gauging applications. In medicine used for diagnosis and treatment in diagnostic radiology, nuclear medicine, radiation therapy and medical radionuclide’s as main branches. While in science and research it is comprise materials science, material irradiation, radiation damage research, crystal color enhancement, tools for physics, research reactors and nuclear power plants experiments and radioisotopes production. Moreover, radiation is applicable irradiation processed articles ,electronics testing, semiconductor – as silicon – production, material characterizations, biological applications, agricultural applications, archaeological applications, and tracer techniques. The workers in these applications are subject to some risks. To minimize these risks and maximize benefits it is necessary to apply radiation protection program to protect those workers. The current paper introduces the main factors for this protection in simply, followed with practical results. Some exposures are acceptable and regulated by the Egyptian Nuclear and Radiological Regulatory Authority (ENRRA).